Congenital medulloblastoma presented in the neonatal period - Patricio García-Espinosa; Max Molina-Ayala; Edgar Botello-Hernández; Estefania Villareal-Garza; Álvaro Barbosa-Quintana (University of São Paulo, 2021)
Congenital medulloblastoma is a rare brain tumor that appears in less than 1% of pediatric patients. Congenital medulloblastoma has a poor prognosis and should be suspected in patients with clinical manifestations of hyporeactivity, slow suction reflexes, and the presence of hydrocephalus. Herein we present the case of a 12-day-old female newborn who developed non-communicative hydrocephalus, hyporeactivity, and hyporeflexia. Magnetic resonance imaging of her brain showed a heterogeneous and cystic mass on the posterior cranial fossa. A suboccipital craniotomy was performed. The histopathologic analysis reported a congenital medulloblastoma. She remained in hospital until her death at 112 days old. This is one of the first case reports with clinical-radiological and pathological documentation. Awareness of this diagnosis can allow prenatal intervention, rendering a better prognosis. This case report exemplifies the importance of good prenatal follow-up.